PENINGKATAN SUMBER DAYA MANUSIA GURU DI SMPI BRAWIJAYA PUNGGING MELALUI BUDAYA LITERASI DIGITAL - Syafaat, Wahyu (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2020)
The development of information technology in the digital era is rapidly increasing causing more abundant digital information resources. The condition of students at school now has a high dependence on information search on the internet. In addition, there are many demands for teachers to fulfill the tasks of digital education administration. Therefore, teachers as educators or instructors in schools must have sufficient digital literacy skills to be able to carry out their duties as educators and educators well. The purpose of this study is to explain and reinforce the importance of improving teacher human resources through digital literacy culture. This research uses a descriptive quantitative approach. Data collection in this study using the questionnaire method was supported by direct interviews. The sampling technique uses multistage random sampling technique. The results of the study show that the level of digital literacy competence of teachers in SMPI Brawijaya based on several aspects of digital literacy competency is relatively high Keywords: Human Resources, Teacher, Digital Literacy.